Analisis Keluaran Daya Listrik Dihasilkan Aliran Pipa 1/2” untuk Pembangkit Listrik Tenaga Mikrohidro dengan Generator DC - Ahmad Farisy; Dedi Ary Prasetya (Science Tech: Jurnal Ilmu Pengetahuan dan Teknologi, 2023)
This experimental research attempts to examine PLTMH on water reservoirs with 1/2" pipes with height variations of 1 meter, 2 meters and 3 meters and the use of several generators installed in series. The test aims to determine the height and number of generators that produce more optimal power.In conducting data analysis, the researchers also employed the descriptive method from Miles and Huberman. The results of the first experimental test were to determine the value of flowrate of 4,166 m3/s and the water pressure about 0.01 MPa at a height of 1 meter, 0.02 MPa at an altitude of 2 meters and 0.03 MPa at a height of 3 meters. The results of the flowrate and water pressure tests were used as a benchmark in testing the PLTMH with 5 types of DC generator test circuits with a load, namely the 12V 3W LED lamp. The result shows, the power is 2.675W and the voltage is 53.50V with a current of 0.050A. It is affected by the water level, the water pressure will increase, consequently, the hydrostatically water pressure hits the turbine blades which affects the rotation of the generator which produces high power.